Paddy Farmers’ Awareness, and Perception Towards Agroforestry Practice and The Effect of Different Agricultural Practices on Selected Soil Properties in Siburan Sarawak - Jacklin, Mathew (Universiti Malaysia Sarawak, 2025)
Agriculture is essential for the survival of humanity, but unsustainable practices threaten its long-term viability. Rice is an important crop as it is a staple food and the main source of income and livelihood, especially for rural communities in Malaysia. Intensive farming activities such as tillage, residue burning and the use of agrochemicals can lead to soil erosion and degradation. Sustainable practices such as intercropping, agroforestry and home gardening are known to improve soil health and reduce environmental impact. Agroforestry has gained popularity due to its ability to counteract the effects of climate change by increasing the resilience of agriculture but also combat food insecurity and land degradation. Therefore, it is crucial to introduce agroforestry practices to farmers to diversify their income sources s and help them adapt to climate change. The aim of this study was to determine the awareness and perception of rice farmers in Siburan, Sarawak towards agroforestry. Moreover, different agricultural practices have different effects on soil properties, so this study also aimed to determine the selected physicochemical properties of soil under different agricultural practices. Data for the first two objectives were collected through questionnaire-based interviews in Kampung Skuduk and Kampung Chupak. 43 responses were obtained, and the data were analysed statistically to interpret farmers’ responses. For the third objective, soil samples from three sites with different agriculture practices were collected and analysed. The samples were then analysed for various soil fertility indicators. The results show that farmers’ knowledge of agroforestry practices was limited, especially among non-agroforestry practitioners. There are no significant income differences between agroforestry practitioners and non-agroforestry practitioners as agroforestry is practised on a small scale and for domestic use as there are no commercial market opportunities for the products. Awareness raising and information dissemination activities are important as lack of awareness hinders the implementation of agroforestry. Furthermore, the respondents have a positive attitude towards agroforestry practices. They expected awareness-raising activities and workshops on agroforestry, which shows that they are willing to learn more about these practices. 80% of respondents who do not practice agroforestry are interested in practicing agroforestry if there are no obstacles. This positive attitude indicates that farmers in the study area are ready and willing to practice agroforestry. Among the land-use systems, agrisilviculture recorded the highest overall soil fertility, as indicated by its superior Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF). This system maintained favourable conditions across multiple soil fertility indicators, including higher organic matter content, better moisture retention, and lower compaction. The soil pH under agrisilviculture was also optimal, contributing to a more balanced soil environment. In contrast, home gardens showed signs of acidification, which corresponded with reduced levels of essential nutrients, ultimately lowering their SEF values. These results emphasise the need to understand how different agricultural practices soil properties and provide practical insights to improve soil management strategies in Siburan, Sarawak. Keywords: Agroforestry, awareness, knowledge, perception, soil properties